Clinical efficacy of atrial fibrillation ablation depending on histological changes in the myocardium - A. E. Shelemekhov; R. E. Batalov; S. Yu. Usenkov; E. A. Archakov; A. M. Gusakova; Yu. V. Rogovskaya; M. S. Rebenkova (Российский кардиологический журнал)
There is a group of patients with so-called idiopathic atrial fibrillation (AF) without the causes of arrhythmia established by a standard examination.Aim. To study the effect of histological changes in the myocardium in patients with idiopathic AF on the effectiveness of ablation.Material and methods. The study included 101 patients with idiopathic AF All patients underwent ablation, during which a myocardial biopsy was performed. Depending on the results of intervention, 3 groups were formed: 1 — no AF within 12 months, 2 — recurrent arrhythmia within first 3 months of follow-up, 3 — recurrent arrhythmia after first 3 months of follow-up. To assess inflammatory changes and the severity of fibrosis, histological and immunohistochemical tests of myocardial biopsies were performed.Results. Histological criteria for lymphocytic myocarditis in group 1 observed in 47,5% of patients, in groups 2 and 3 in 27,3% and 25%, respectively. Infiltration of less than 7 cells per 1 mm2 by CD3+ lymphocytes prevailed in group 3. The activity of inflammation in the studied groups did not significantly differ. The minimum severity of fibrosis was significantly less frequently recorded in group 1 than in group 2 and 3. Nonexpression of viral antigens in the first group was significantly less common than in the second and third groups. Moreover, the combination of expression of enterovirus VP1 and human herpesvirus 6 antigens was significantly more often recorded in the first group. Positive correlation was found between the expression of viral antigens and markers of endo- and myocardial fibrosis.Conclusion. The primary risk factor for recurrent arrhythmia was the initial stage of fibrosis, while inflammatory changes and viral infection were not risk factors. The presence of viral antigens in the myocardium had an indirect effect on the clinical outcome.